2009
DOI: 10.1590/s1415-43662009000600020
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do conforto térmico e desempenho de frangos de corte sob regime de criação diferenciado

Abstract: Esta pesquisa foi conduzida com o objetivo de avaliar três sistemas de criação para frangos de corte industrial, visando caracterizar o ambiente térmico e o desempenho animal. O experimento foi realizado no decorrer de 42 dias, desenvolvido em módulos de produção, divididos em 15 boxes com 10 aves por box, submetidas a três sistemas de criação: semi-confinado com 3 m² por ave de área de piquete (SC 3), semi-confinado com 6 m² por ave de área de piquete (SC 6) e confinamento total (CONF). O delineamento experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
18

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 15 publications
0
21
0
18
Order By: Relevance
“…Laying quails raised within the TCZ can express their best productive characteristics (Nazareno et al, 2009), because maintaining RR within physiological levels is fundamental, especially to maintain blood pH normal and avoid problems such as blood alkalosis. The values in the present study were lower than those reported by Costa et al (2012), who studied physiological indicators in the production of broiler chickens and observed minimum and maximum RR of 46.83 and 58.96 mov min -1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Laying quails raised within the TCZ can express their best productive characteristics (Nazareno et al, 2009), because maintaining RR within physiological levels is fundamental, especially to maintain blood pH normal and avoid problems such as blood alkalosis. The values in the present study were lower than those reported by Costa et al (2012), who studied physiological indicators in the production of broiler chickens and observed minimum and maximum RR of 46.83 and 58.96 mov min -1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…It should be pointed out that CT is one of the physiological parameters used to determine if the animal is or not in thermal balance with the environment (Santos et al, 2006), because it is a mechanism used by birds to release the stored heat. Nazareno et al (2009) also cite CT values around 41 and 42 ºC in broiler chickens raised in paddock and confined systems.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A densidade das aves por metro quadrado, também deve ser observada, para não haver estresse calórico (NAZARENO et al, 2009).…”
Section: Resultsunclassified
“…Este aumento da frequência respiratória resulta em perdas excessivas de dióxido de carbono (CO 2 ). Assim, a pressão parcial de CO 2 (pCO 2 ) diminui, levando a redução nas concentrações de acido carbônico (H 2 CO 3 ) e dos íons de hidrogênio (H + ) (MARCHINI et al, 2007;NAZARENO et al, 2009). Segundo os mesmos autores, em resposta compensatória, os rins aumentam a excreção de HCO 3-e reduzem a perda de H + na tentativa de manter o equilíbrio ácido-base da ave. Tal alteração é denominada alcalose respiratória.…”
Section: Fisiologia Do Estresse Pelo Calorunclassified